Novel value chain upgrading strategy for valorization of heirloom rice in Philippines - CGIAR Research Program on Rice (2021)
The proof of concept can be used by policymakers to develop strategies for valorizing heirloom rice through place branding, geographic indicators, product differentiation, and promotion of dietary shifts.